2012
DOI: 10.3329/bjsir.v47i3.13065
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence of hepatitis A in Bangladesh

Abstract: Hepatitis A (HAV) infection is caused by the hepatitis A virus which is transmitted through the fecal-oral route. Life long protective antibodies are present after infection. The number of cases of adult hepatitis A has progressively been increasing during the last several decades in Bangladesh. In addition, the pattern of age-specific seroprevalence of anti-HAV has changed with economic growth. The prevalence of anti-HAV in 20-40 year age range has declined rapidly during the last 3 decades. As a result, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…151 As a result, this age group has a high risk for HAV infection, and clinically overt hepatitis A is increasing in adolescents and adults. 152 Although the endemicity of HAV seems to be decreasing, adolescents and adults with high socioeconomic status remain at particularly high risk of symptomatic and severe illness, because individuals of high socioeconomic status have a low chance of HAV infection as children. 152 The clinical manifestations of hepatitis A depend on the age of the host: less than 30% of infected young children showed symptomatic hepatitis, whereas about 80% of infected adults had symptoms of severe acute hepatitis.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
See 1 more Smart Citation
“…151 As a result, this age group has a high risk for HAV infection, and clinically overt hepatitis A is increasing in adolescents and adults. 152 Although the endemicity of HAV seems to be decreasing, adolescents and adults with high socioeconomic status remain at particularly high risk of symptomatic and severe illness, because individuals of high socioeconomic status have a low chance of HAV infection as children. 152 The clinical manifestations of hepatitis A depend on the age of the host: less than 30% of infected young children showed symptomatic hepatitis, whereas about 80% of infected adults had symptoms of severe acute hepatitis.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
“…There have been substantial advances in research on liver diseases in Bangladesh and several epidemiological studies have been published in the past two decades. [56][57][58][59][60][61][62]149,150,[152][153][154][155][156][218][219][220]223,[406][407][408] Still, baseline data on incidence, prevalence, risk factors, natural history, and the changing epidemiology of various causes of liver diseases need to be generated. Studies are needed to develop cheap, accessible, point-of-care testing for HBV and HCV, and on preventive measures and new drug treatments for NAFLD.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
“…5 I n m a ny developing countries of Africa, Asia and Latin America, most infections occur by 5 years of age where seroprevalence approach 90-100% by 10-15 years of age. 1 In Africa, Hendricks et al 6 showed anti-HAV positivity of >90% among the 5-10 year age group among lower class black children. In developing countries, low economic status, high crowding and inadequate water treatment contribute to a high endemicity pattern; more than 90% of the population has acquired natural immunity before 10 years of age, and often shows asymptomatic forms.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis A is an enterically transmitted viral disease world wide distributed. 1 Acute viral hepatitis caused by HAV is an acute, self-limiting infection. 2 Hepatitis A virus infection is very common in early childhood and most of the infections are asymptomatic or mildly symptomatic.…”
Section: Introductionmentioning
confidence: 99%